PERKEMBANGAN TENAGA KERJA WANITA DI SEKTOR INFORMAL: HASIL ANALISA DAN PROXY DATA SENSUS PENDUDUK - Hakim, Lukmanul (Jurnal Ilmiah Among Makarti, STIE AMA Salatiga, 2011)
This article analyses the trend of women workers in the informal sector in Indonesia over the last 20 years. The data shows that more and more women have entered the workforce and that the informal sector has the capacity to absorb the majority of the women workers. Data for the 1990s shows that the majority of women in the labour force were self-employed, and it is predicted that this is also will be the trend for women workers in the future. This self-employed trend is probably more attractive to women in the labour force because in this way they are more flexible in combining income-earning activities and their household chores.